Assessment of Maternal Serum Levels of Vascular Endothelial Growth Factor and Placental Growth Factor in Threatened Abortion: A Case Control Study - Sugandha Dev; Alpana Singh; BD Banerjee; Gita Radhakrishnan; Rachna Agarwal (Journal of Clinical and Diagnostic Research, 2020)
Introduction: Vascular Endothelial Growth Factor (VEGF) and Placental Growth Factor (PlGF) are implicated in the pathophysiology of Threatened Abortion (TA). VEGF family regulates placental angiogenesis and maternal spiral artery remodelling whereas PlGF is an important regulator of decidual angiogenesis and is a mediator of trophoblast function. Earlier studies have investigated role of these markers in patients with TA but no definite consensus has been reached. Moreover there is limited data from our population. Aim: To assess the maternal serum levels of VEGF and PlGF in patients with TA compared to uncomplicated pregnancy. Materials and Methods: This was a case control study conducted in a tertiary care hospital of Northern India in which total 40 TA patients and 40 controls were analysed. A 3 mL of peripheral blood sample was collected from each case and control. The plasma was separated and quantification of VEGF and PlGF was done by using ELISA kits in cases and in age and gestational age matched controls. Results: Serum VEGF level was significantly lower in cases compared to controls (30.65±9.41 pg/mL vs. 64.55±16.67 pg/mL, p<0.001) irrespective of their gestational age. TA patients also had lower serum PlGF level (263.54±68.108 pg/mL vs. 341.83±112.704 pg/mL, p<0.001). But no definite trend was found in VEGF and PlGF levels with increasing gestational age. Conclusion: Maternal serum VEGF and PlGF level was low in patients with TA compared to uncomplicated pregnant women regardless of gestational age.